(untitled) (CIPEEX, 2025)
This paper examines whether reversing the order set by article 400 of the Brazilian Code of Criminal Procedure—under which the defendant’s examination closes the evidentiary stage after witness testimony—amounts to nullity when testimony is taken by carta precatória (letters rogatory), a situation in which issuing the letter does not stay the criminal case. It is a doctrinal and case-law review addressing the last-act nature of the defendant’s examination, the continuity of proceedings before the requesting court, and the requirement of demonstrable prejudice. The aim is to state practical criteria for recognizing (or rejecting) nullity in carta precatória scenarios, in light of article 563 (pas de nullité sans grief) and timeliness rules (arts. 571–572). The method consisted of a critical analysis of scholarship and precedents on the order of acts, evidence gathered by letters rogatory, and preclusion. The findings indicate that: (i) inversion resulting from letters rogatory, by itself, does not create nullity; (ii) any nullity requires proof of actual prejudice and must be raised at the hearing or at the first opportunity, on pain of preclusion; and (iii) the judge must safeguard adversarial proceedings and the right to be heard, including reopening statements when warranted. It concludes that article 400 is observed without halting the case due to letters rogatory and that nullity arises only upon proof of concrete procedural harm.